Pembuatan Bibliografi Beranotasi terhadap Objek Kajian Keminangkabauan dalam Jurnal Suluah menggunakan Format Modern Language Asociation di Balai Pelestarian dan Nilai Budaya Sumatera Barat - Rusdi, Syifa Aini; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
The purpose of this paper to help visitor and librarian at the Preservation institute and Cultural Values of West Sumatra to investigate an information or retrieval information. In the production of this paper we describe the stages of productionannotated bibliography Journal Minanngkabau Suluah with the subject in theCentral Library and the preservation of Cultural Values of West Sumatra. This paper uses descriptive research method that aims to create a description,representation or illustration in a systematic, factual and accurate information onthe facts, nature and the relationship between the phenomenon investigated.Stages of Creation bibliography are: 1) determination of the object of studykeminagkabauan title; 2) the collection of material objects in Suluahkeminangkabauan Journal; 3) the selection of library materials; 4) Typing objectmaterial keminangkabauan in Journal Suluah; 5) grouping or classification; 5)indexing; 7) inspection of the final manuscript bibliography. the obstacle inwriting of bibliography are: 1) Library and Cultural Values Preservation HallWest Sumatra has a narrow room, less in infrastructure and materials andcollections that much; 2) a search of materials not in accordance with theconsecutive years; 3) Wasting time; 4) understand about the differenciate betweenin Minangkabau word and West Sumatra words ; 5) Typing is concerned. Effortsare being made are: 1) preserving and arrange library materials a) improvelighting; b) the humidity of the room; c) remove books that have several copies 2)the preparation according to the classification of library materials; 4)understanding of the word Minangkabau Cultural Studies; 5) Do reexamination.Keyword: bibliography, annotation, journals